2021
DOI: 10.3390/su13010392
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Approach to Integrate and Evaluate Sustainable Development in Higher Education. The Case Study of the University of the Basque Country

Abstract: Since the United Nations (UN) approved the Agenda 2030 for Sustainable Development in 2015, higher education institutions have increasingly demonstrated their commitment by supporting several initiatives. Although a great deal of progress has been made, there is still a lack of integrative approaches to truly implement Sustainable Development Goals (SDGs) in higher education. This paper presents a practical case that illustrates how to design and articulate SDGs within an institutional setting adopting a holis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
63
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 17 publications
1
63
0
4
Order By: Relevance
“…Despite progress, there is still a lack of integrative approaches to truly implementing the Sustainable Development Goals in higher education. It is on this basis that Sáez de Cámara, Fernández and Castillo-Eguskitza [24] carried out a case study at the University of the Basque Country (UPV/EHU) proposing a holistic approach involving the whole institution. After defining the path of analysis (mapping, mainstreaming, diagnosis and definition to estimate the situation taking into account the SDGs) they concluded that it is crucial that the university defines and endorses indicators and values them in order to bring about a change of culture in the organisation as a whole, something traditionally difficult in this type of organisation.…”
mentioning
confidence: 99%
“…Despite progress, there is still a lack of integrative approaches to truly implementing the Sustainable Development Goals in higher education. It is on this basis that Sáez de Cámara, Fernández and Castillo-Eguskitza [24] carried out a case study at the University of the Basque Country (UPV/EHU) proposing a holistic approach involving the whole institution. After defining the path of analysis (mapping, mainstreaming, diagnosis and definition to estimate the situation taking into account the SDGs) they concluded that it is crucial that the university defines and endorses indicators and values them in order to bring about a change of culture in the organisation as a whole, something traditionally difficult in this type of organisation.…”
mentioning
confidence: 99%
“…Although the current understanding of effective methods for integrating the 2030 Agenda from a holistic approach still has its limits, more and more experiences are emerging from universities to undertake transformative projects that broaden their approach beyond the purely pedagogical. The University of the Basque Country (UPV/EHU) is a public university that considers the 2030 Agenda and the SDGs as a structuring model [7]. For this reason, the UPV/EHU's strategic plan for 2018-2021 included the mandate to develop its own agenda for the development of the SDGs from an integral and global perspective [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the UPV/EHU has launched the IKD i 3 teaching-learning model, which consists in multiplying learning through research and sustainability, so that new processes and products are made possible. The UPV/EHU has made a commitment to the future, its roadmap having a time perspective up to 2030, although in 2025 an evaluation will be made that will establish the lines of work to be followed (Sáez de Cámara et al 2021).…”
Section: Introductionmentioning
confidence: 99%